Numerical study of potential heat flux mitigation effects in the TCV snowflake divertor. (1st March 2016) - Lunt, T; Canal, G P; Duval, B P; Feng, Y; Labit, B; McCarthy, P; Reimerdes, H; Vijvers, W A J; Wischmeier, M
Abstract: We report on EMC3-Eirene simulations of the plasma and neutral particle transport the TCV boundary layer of a series of snowflake (SF) equilibria characterized by the normalized poloidal flux coordinate of the secondary X-point x 2 . We refer to a snowflake plus (SF + ) for, a snowflake minus (SF − ) for and a single-null (SN) for . Four effects are identified that have the potential to mitigate the heat flux density at the outer strike point in a LFS SF − where x 2 is located on the low field side of the primary X-point x 1 : (1) a scrape-off layer heat flux splitting, (2) an impurity radiation cloud forming at x 2 (3) the increased connection length to the outer target and (4) increased transport between x 1 and x 2 . The LFS SF − is thus expected to tolerate a larger power flux over the separatrix than a comparable SN configuration.